Exploring Physician Well-Being: A Bibliometric Analysis of Mental Health - Kumareswaran, Suriya; Sundram, Bala Murali; Thurairasu, Vanitha (Kesmas, 2025)
This bibliometric study examined the evolving research landscape on physician mental health from 2010 to 2023, analyzing key themes, publication trends, and global contributions. A total of 3,360 articles, including 3,137 original research and 223 reviews, were sourced from Web of Science and Scopus. Findings revealed a significant increase in research output, particularly during the COVID-19 pandemic, with burnout, depression, and anxiety emerging as dominant themes. The US accounted for most publications, while research from low- and middle-income countries remains limited, indicating a substantial global disparity. Thematic analysis highlighted variations in burnout assessment methodologies, underscoring the need for standardized evaluation tools. This study also identified systemic challenges, including excessive workload, hierarchical workplace structures, and inadequate institutional support, as major contributors to physician distress. Technological inefficiencies, particularly in electronic health record systems, exacerbated administrative burdens and physician dissatisfaction. Recommendations include developing standardized mental health assessment frameworks, expanding study in underrepresented regions, and implementing organizational policies to enhance physician well-being. This review provides critical insights for policymakers, healthcare institutions, and researchers, offering a foundation for targeted interventions and evidence-based reforms to improve physician mental health globally.